Pendidikan Kewarganegaraan Sebagai Sarana Pembentukan Identitas Nasional - Rima Volyna Munthe; Ruth Hanna Apriani Sihombing; Tebi Tafianta Banjarnahor; Yulia Fanissah Sihotang; Sri Yunita (Universitas 17 Agustus 1945 Semarang, 2024)
Citizenship education is education that reminds us of the importance of the values ​​of the rights and obligations of citizens. Everything that is done must be in accordance with the goals and ideals of the nation and not deviate from what is expected. Citizenship education is an educational program that has political democracy at its core which is expanded with other sources of knowledge, positive influences from school education, society and parents. The method used in this research is a qualitative method with a literature study approach. The data collection technique in this research is analysis of literature, books, scientific articles, and various other scientific reading sources related to the material discussed in this research, namely citizenship education as a means of forming national identity. Citizenship Education has a strategic role in preparing intelligent citizens. Law Number 20 of 2003 concerning the National Education System has regulated Citizenship Education for formal education starting from primary, secondary and higher education, and also for non-formal education. The upbringing of Citizenship Education in formal education institutions is aimed at students, designed curricularly and processed through learning activities. Citizenship education is expected to be a guide in instilling character and a sense of love for the country for the formation of Indonesian national identity. However, the presence of globalization in people's lives certainly has both positive and negative impacts. One of the positive impacts of globalization is that it is easier for people to find information or phenomena that occur throughout the world easily and quickly.